Popular Gospel in the Caribbean: Gospel Video as a Site of Meaning - Best, C. (Journal for the study of religion, 2007)
This essay provides a perspective on aspects of the current trends withinpopular gospel culture in the Caribbean. It represents an importantintervention, since there is relatively little published about this subject inacademic and critical journals. This essay, therefore, introduces the readerto Caribbean popular gospel culture; provides an overview of the state ofCaribbean gospel music culture; lists some of the global trends within gospelculture; zeros-in on the gospel music video as a site of cultural expression,and examines two main music video templates in western popular gospelculture; and shows how the Caribbean’s leading chorale group of the late1990s and early 2000s responds to and transgresses these western models.All in all, the essay provides a description of the kinds of influences thatcurrently drive contemporary Caribbean gospel-music culture.